THE REASONING BEHIND THE USE OF PRACTICAL ACTIVITIES IN THE EDUCATION OF STUDENTS WITH MODERATE/SEVERE DISABILITIES - Prudņikova, Ilga; Bruveris, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper examines the background to the use of experiential learning with students with moderate/severe disabilities. The role of practical tasks and activities in the education of these students is an important one. There has been a change in the concept of learning, away from the behaviourist notions of teachers as purveyors of knowledge and students as passive receivers. Cognitive, humanistic, social and constructivist learning theories stress the importance of making sense or meaning from experiences. A review of current and past theories of cognitive development focusing on the role of experiential learning, the impact of the surrounding environment, active participation, scaffolding support for learning, the impact of emotions and the development of attitudes as well as the place of interaction, reflection and feedback is linked to implications for practice.